The Impact of the Grain for Green Program on Farmers’ Well-Being and Its Mechanism—Empirical Analysis Based on CLDS Data - You, Zhe; Wu, Tong; Gong, Mengqi; Zhen, Shiqi; Cheng, Jinhua (Frontiers in Ecology and Evolution, 2022)
This paper found the optimization direction of ecological compensation project from the perspective of farmers' well-being. Based on the data of 2016 China Labor Force Dynamic Survey (CLDS2016), this paper uses the ordered Probit model to investigate the impact of the Grain for Green Program on farmers' subjective well-being. The study found that the Grain for Green Program significantly reduced farmers' subjective well-being. The regression results after using the alternative explanatory variables to mitigate endogenous errors are still robust. Further research found that the Grain for Green Program ultimately inhibited the subjective well-being of farmers by reducing the subjective perception of air, soil and noise pollution, intensifying the subjective perception of water pollution and reducing the per capita income of households. In the new round of the Grain for Green Program in the "14th Five-Year Plan" period, it is advisable to increase the intensity of income compensation, strengthen supervision to ensure the payment of compensation to households, and control the scale of the project based on ecological foundation, so as to improve the well-being of farmers.